Mapping the global landscape of Roblox-based learning research in a bibliometric analysis - Trisniawati Trisniawati; Nelly Rhosyida; Krida Singgih Kuncoro; Devi Septiani; Fitria Sulistyowati; Betty Kusumaningrum; Sony Yunior Erlangga; Dhimas Nur Setyawan; Zohaib Hassan Sain (Universitas Sarjanawiyata Tamansiswa, 2025)
Roblox has emerged as a prominent platform-based learning environment that bridges gamification, immersive virtual worlds, and interactive pedagogies. Despite its growing adoption in educational contexts, the global research landscape on Roblox Education has not yet been systematically mapped. This study aims to analyze the structure, dynamics, and thematic evolution of scholarly publications related to Roblox-based learning within the Scopus database from 2020 to 2025. Using a bibliometric approach supported by performance analysis and science mapping techniques in Biblioshiny, this study examines 37 documents indexed in 26 sources, involving 214 authors and an annual growth rate of 58.49%. The findings reveal high collaboration intensity (8.78 co-authors per document) and considerable academic influence, with an average of 69.97 citations per publication. Korea, the United States, Indonesia, India, Spain, and China emerged as leading contributors to the field. Science mapping shows four dominant thematic structures: (i) metaverse and virtual reality as motor themes; (ii) Roblox, education, artificial intelligence, and e-learning as basic themes; (iii) educational alternatives and niche digital environments as highly developed but isolated themes; and (iv) emerging or declining themes, including avatars, computational theory, and video games. Trend analysis indicates a strong shift from conventional e-learning toward immersive, metaverse-driven, and game-based pedagogies between 2022 and 2024. Reference spectroscopy highlights 2020–2023 as a pivotal period marked by rapid theoretical expansion following global pandemic-related digitization. Overall, the findings demonstrate that Roblox Education represents a rapidly maturing and multidisciplinary research domain, with substantial potential to support experiential learning, digital creativity, and the remediation of learning loss. Implications for future research include the integration of adaptive AI, immersive assessment frameworks, and curriculum-level adoption of platform-based learning.